Implications of Mangrove Planting For Ecotourism Prospects in Kartikajaya Village, Patebon District, Kendal Regency - M. Irsyadul Ibad; Cucu Wulan Nafi Kustiani; Qonitatin Wafiyah; Salma Faizatun Solikhah; Muhammad Nur Alfan Kamal; Hanik Rosyida (Universitas Kristen Indonesia Toraja, 2024)
The community service program in Kartikajaya Village aims to utilize local economic potential by making mangrove planting a tourist attraction. The village has suitable geographical conditions for ecotourism development, but the lack of community awareness and understanding of the benefits of mangroves is a major challenge. The program involves the local community in mangrove planting and maintenance activities, as well as providing education on the importance of mangroves in maintaining the balance of coastal ecosystems and increasing the village's tourism attractiveness. The results of this program showed an increase in community awareness of the importance of environmental conservation, as well as an increase in the number of tourist visits to the village. Thus, mangrove planting not only serves as an environmental conservation effort, but can also make a positive contribution to the economy of the surrounding community through the development of river cruising ecotourism.